Investment funding programs on dairy farms in Hajdú-Bihar County - Csatári, Nándor; Vántus, András (Acta Agraria Debreceniensis, 2018)
The dairy farming sector needs constant modernization of its buildings, machines and technology in order to maintain its competitiveness and productivity. For the greater scale investments, these companies try to apply for state funds in addition to their own financial sources. Therefore, the investment support system plays a great role by improving the competitiveness and modernity of these farms. In the last 10 years, 7 funding programs were available for dairy farms. In this research, 25 dairy farms were interviewed in Hajdú-Bihar County. The examined farms cover more than 50% of the milk production in Hajdú-Bihar County. The survey questions focused on the investment funding program use of farms between 2007 and 2017 and renewable energy investments including all programs. The results show how many tenders were submitted, how many were successfully evaluated and completed. All farms had at least two successfully evaluated projects. A correlation was found between completed projects by farm size and completed projects. The connection of the modernity index of dairy farms and the completed projects was also shown.